2004
DOI: 10.1097/00006223-200401000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Community Partnerships for an LPN to BSN Career Mobility Project

Abstract: Based on a 6-year, learn and earn curriculum, the authors report on a year-old project that assists licensed practical nurses (LPNs) to obtain a baccalaureate degree in nursing (BSN). Partnerships with 4 area healthcare agencies employing LPNs were developed to support students with full or partial tuition reimbursement and work schedules to accommodate classes. Key university staff in the offices of admissions, financial aid, adult programs and services, and nursing advisement are assigned to this student gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…For example, utilizing and validating students’ previous RPN knowledge was shown to successfully ease students into the curriculum (Adelman, ; Hylton, ; Melrose & Gordon, ). Faculty–student and peer–peer mentorships were also successfully used to integrate students into the social and academic milieu of the educational institution, overcome the challenge of managing multiple conflicting family and school obligations, and impart the technical skills and knowledge needed to succeed in a bridging program (Claywell, ; Hammond, Davis, Marlin, & Montgomery, ; Hutchinson et al., ; Hylton, ; Melrose & Gordon, ; Miller & Leadingham, ; Nichols et al., ; Porter‐Wenzlaff & Froman, ; Ralph et al., ; Ramsey, Merriman, Blowers, Grooms, & Sullivan, ; Rapley et al., ; Wendel, ). In addition, providing students with ongoing opportunities to reflect on and review their personal learning goals successfully sustained student motivation in the bridging program (Melrose & Gordon, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, utilizing and validating students’ previous RPN knowledge was shown to successfully ease students into the curriculum (Adelman, ; Hylton, ; Melrose & Gordon, ). Faculty–student and peer–peer mentorships were also successfully used to integrate students into the social and academic milieu of the educational institution, overcome the challenge of managing multiple conflicting family and school obligations, and impart the technical skills and knowledge needed to succeed in a bridging program (Claywell, ; Hammond, Davis, Marlin, & Montgomery, ; Hutchinson et al., ; Hylton, ; Melrose & Gordon, ; Miller & Leadingham, ; Nichols et al., ; Porter‐Wenzlaff & Froman, ; Ralph et al., ; Ramsey, Merriman, Blowers, Grooms, & Sullivan, ; Rapley et al., ; Wendel, ). In addition, providing students with ongoing opportunities to reflect on and review their personal learning goals successfully sustained student motivation in the bridging program (Melrose & Gordon, ).…”
Section: Resultsmentioning
confidence: 99%
“…Curriculum delivery through online programs (Murdock, ; Ralph et al., ; Rapley et al., ), and flexible, efficient curriculum plans and class schedules may further help bridging students balance multiple life roles (Hutchinson et al., ; Nichols et al., ; Ramsey et al., ). Moreover, it has been suggested that RPN‐to‐RN bridging programs can better prepare students for the RN role by providing clinical practicum experiences in diverse practice settings (Nichols et al., ; Porter‐Wenzlaff & Froman, ) and providing students with opportunities to engage in collaborative, community‐based research projects (Nichols et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vocationally prepared Licensed Practical Nurses (LPN's) who enter an online university to continue their education by earning a Bachelor of Nursing (BN) degree face unique challenges (Melrose and Gordon, 2008;Porter-Wenzlaff and Froman, 2008;Ramsey et al, 2004). And yet, educational research examining both the barriers that these adult learners face and the strategies they implement to overcome them is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Brown (2005) suggested that students began their studies, which were online, with some unrealistic expectations regarding the program's rigor and flexibility. Anecdotally, Ramsey, Merriman, Blowers, Grooms and Sullivan (2004) stated that regularly scheduled role transition seminars were needed in their LPN to RN program and that early identification of students at academic risk was important. Texts are available for facilitating these kinds of seminars (Claywell, 2003b;Duncan & DePew, 2005;Ham, 2001;Harrington & Terry, 2003).…”
mentioning
confidence: 99%